Study on the Symbols "Sheng" and "Zu" in Hongshan Culture Rock Paintings - Tie, Zhao; Yushu, Zhou (Pacific International Journal, 2024)
Fertility and ancestor worship are important expressions of social ecology and natural views in Hongshan culture. Based on archaeological findings, numerous archaeological remains related to fertility have been found in Hongshan culture sites. These artifacts reflect the worship, respect, and emphasis on female fertility by the people of Hongshan culture. Additionally, Hongshan culture demonstrates reverence for its ancestors. Archaeological studies have uncovered numerous sacrificial sites and offerings, indicating the reverence and sacrificial activities towards ancestors during the Hongshan culture period. Ancestor worship evolved from primitive totem worship in transitioning from matrilineal to patrilineal societies. Recent surveys and field investigations of rock paintings in the Chifeng region have identified 130 individual "Sheng" and "Zu" character rock paintings, meticulously documented through data recording. Comparative studies of similar "Sheng" and "Zu" character symbols in artifacts and rock paintings from the Hongshan culture period reveal the culture’s emphasis on fertility, ancestor worship, and reverence for life. These beliefs and cultural traits were fully expressed in Hongshan culture and profoundly influenced subsequent cultural developments and people’s values. This study enhances our understanding of the beliefs and values of the people of Hongshan culture, their regard for life, fertility, and ancestors, and the role of these symbols in cultural transmission.